Belajar dari Fenomena Maw?l? - Hairul Puadi; Nur Qomari (MAQASHID Jurnal Hukum Islam, 2018)
Maw?l? was born from the oppression and discrimination of the Umayyad Regime. They emerged as a new political force and as an opposition which eventually helped to overthrow the Umayyad Dynasty. This is a further result of the Bani Umayyad's political policies in upholding Arab supremacy over the non-Arab Muslim community. Realized or not, sharp segregation and separation in terms of social, economic up to worship (ritual) gave birth to a new phenomenon in the world of the political arena of the Umayyad regime. Arab supremacy can indeed be enforced, but greater movement and strength in their bodies are ready to tear them down at any time. The oppression, discrimination and treatment as a second class society under the domination of the Arab Muslims they received not only made them hate the Umayyad regime but moreover they were anti-Arab; trying to oppose the Arabism system.